Current state and perspectives of research on construction management and mechanisation in Poland - Kapliński, Oleg; Werner, Witold; Kosecki, Andrzej; Biernacki, Janusz; Kuczmarski, Franciszek (Journal of Civil Engineering and Management, 2002)
Current and intended research on construction management and mechanisation in Poland is the focus of this article. The discussion comprises four subject groups: investment process organisation, construction company operation, organisation and management methods, and mechanisation—including automation and robotisation in construction industry. Within all subject groups, an overview of the subject and analysis of the research state, as well as priority research trends have been presented. Frist Published Online: 30 Jul 2012